Determination of avibactam and ceftazidime in human plasma samples by LC–MS. (July 2015) - Sillén, Henrik; Mitchell, Richard; Sleigh, Rebecca; Mainwaring, Guy; Catton, Katherine; Houghton, Richard; Glendining, Karen
Aim: Avibactam, a novel non-β-lactam β-lactamase inhibitor co-administrated with the β-lactam antibiotic ceftazidime, is in clinical development. The need to evaluate its PK and PD requires accurate and reliable bioanalytical methods.Methods: We describe LC–MS/MS methods for the determination of avibactam and ceftazidime in human plasma. Avibactam was extracted using weak anionic exchange solid-phase extraction and analyzed on an amide column. Ceftazidime was extracted using protein precipitation and analyzed on a C18 column. Calibration curves were established over 10–10, 000 ng/ml (avibactam) and 43.8–87, 000 ng/ml (ceftazidime).Results & conclusion: Method validation, cross-validation between three laboratories and incurred sample re-analysis demonstrated method robustness. The methods were successfully applied to multiple clinical studies.